PENURUNAN KEMAMPUAN LITERASI DAN NUMERASI PADA ANAK SEKOLAH DASAR - Dina Lastria; Dini, Imam Mahdi Alfarezi, Lusiana, Lira Adawiyah, Nur Denisa, Selvi, Sriliza (CV. ADIBA AISHA AMIRA, 2026)
This study aims to determine the decline in literacy and numeracy skills in elementary school children. Literacy and numeracy are basic skills that are very important for students in the learning process. However, in practice, there are still many elementary school students who have difficulties in reading, writing, and arithmetic. The research method used is a data collection method with Literature study techniques. The results of the study show that the decline in literacy and numeracy is influenced by pedagogical, social, technological, and educational policy factors. Therefore, collaboration between schools, families, and the government is needed to improve the quality of literacy and numeracy of students